Butterfly Abundance and Diversity in Different Habitat Types in the Usangu Area, Ruaha National Park - Evaline J. Munisi; Emmanuel H. Masenga; Ally K. Nkwabi; Halima R. Kiwango; Eblate E. Mjingo (Psyche: A Journal of Entomology)
Insects are key fauna species that respond quickly to disturbances and environmental changes. They act as good indicators of habitat, community, or ecosystem quality. Among the great diversity of insects, butterflies stand as ideal bio-indicators for ecosystem function and are sensitive to changes in habitat composition and structure. This study was carried out to examine the diversity and abundance of butterflies across the restored habitats in Usangu area part of Ruaha National Park (RUNAPA) from May 2022 to June 2022 using the walking transect method supplemented by sweep nets and butterfly baited traps. A total of six transects of 1 km in length were laid in the four main habitat types selected in Usangu area including grassland, Miombo woodland, Vachellia/Commiphora woodland, and riverine forest. Searches were conducted in the morning and evening. The Miombo woodland and riverine forest habitats exhibited relatively higher species diversity, richness, evenness, abundance, and a higher number of habitat-restricted species, while Vachellia/Commiphora woodland and grassland habitats recorded the lowest diversity and abundance as well as the lowest number of habitat-restricted species. Family Nymphalidae was the most dominant followed by Pieridae while Papilionidae and Hesperiidae were scarce in the study area. This study clearly shows the importance of Miombo woodland and riverine forest habitats in sustaining rich butterfly diversity and abundance in Usangu area. The two habitats must be effectively managed and conserved for sustaining ecological health and integrity of Usangu area. The Usangu area’s Miombo woodland and riverine forest habitats have immense potential for butterfly tourism and they can offer an excellent opportunity to promote conservation efforts and raise public awareness. However, it is crucial to monitor these habitats closely as any environmental changes that may occur could harm the butterfly diversity and abundance in the area. Preserving this wilderness to maintain a thriving butterfly population is of utmost importance.